Genetic characterisation and population structure analysis of indigenous and exotic eggplant (Solanum spp) accessions using microsatellite markers. Issue 1 (2nd January 2021) - Nandi, Laxman L.; Saha, Partha; Behera, T.K.; Lyngdoh, Y.A.; Munshi, A.D.; Saha, N.D.; Hossain, Firoz; Bhowmik, Arpan; Pan, R.S.; Verma, Aakriti; Tomar, B.S.
ABSTRACT: In this study, a total of 20 simple sequence repeat (SSR) markers were used to study the genetic diversity and population structure among 60 accessions of eggplant. Out of 20 SSR markers, 15 were found to be polymorphic which were subjected to statistical analysis by Power Marker and NTSYSPc software. The polymorphic SSR markers generated 46 alleles with an average of 3.06 alleles per locus. The PIC value varied from 0.12 to 0.47. The marker emf21N03 was most informative with PIC value of 0.57. The UPGMA-based dendrogram classified all the accessions into two major clusters comprising cultivated accessions and wild progenitor in cluster I and other wild accessions in cluster II. The PCA plot separated the accessions into four quadrangles where unexploited wild accessions presented in second quadrant. Population structure analysis showed 6 sub- populations with 16 accessions in population I, 12 accessions in population II, 11 accessions in population III, 5 accessions in population IV, 12 accessions in population V and 4 in population VI. The subpopulation IV had all pure individuals. These findings will provide new insights in genetic resources conservation and exploitation of genetic diversity of eggplant germplasm in breeding programme.